The Effect of External Debt on Real Economic Sector in Selected CESEE Countries - Ramin Bashir Khodaparasti; Reza Mohammadpour (Amfiteatru Economic Journal, 2016)
Previous studies indicated different results regarding the impact of external debt on economic growth in various countries. These different results may be due to the non-linear impact of external debt on real economic sector. The investigation of a non-linear and dynamic relationship can help governments make appropriate policies versus external debt. In this regard, this paper investigates the impact of external debt on real economic sector in selected countries from central, eastern and south-eastern Europe countries during the period 2000-2014. Investigation in this paper contributes to the literature by covering the non-linear and dynamic relationship to know whether external debt affects the real economic sector of selected CESEE countries. The results of the Generalized Method of Moments based on a dynamic panel data indicate that the impact of external debt on gross domestic product was negative and significant in mentioned countries. Therefore, external debt should be properly applied in which increase the investments with high rate of return. Our empirical findings send a warning about the need to keep the external debts under control.
Keywords: C33; F34; H62; 330; external debt; real economic sector; dynamic panel data; CESEE